2020
DOI: 10.1101/2020.03.28.20045955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medical treatment of 55 patients with COVID-19 from seven cities in northeast China who fully recovered: a single-center, retrospective, observational study

Abstract: Background: COVID-19 is an emerging disease caused by the SARS-CoV-2 virus; no specific medication has been identified to date. We aimed to investigate the administered medications and intervention times for patients who completely recovered from COVID-19. Methods: This single-center, retrospective, and observational study included 55 patients with COVID-19 who were transferred to Shenyang Sixth People's Hospital between January 20 and March 15, 2020. Demographic information, symptoms, laboratory indicators, t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 12 publications
0
36
0
1
Order By: Relevance
“…After evaluating 62 full-text articles for eligibility, 53 full-text articles were further excluded. Finally, 9 studies from different provinces/cities [6,[18][19][20][21][22][23][24][25] were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…After evaluating 62 full-text articles for eligibility, 53 full-text articles were further excluded. Finally, 9 studies from different provinces/cities [6,[18][19][20][21][22][23][24][25] were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 43 studies including 10,676 COVID-19 patients (confirmed by laboratory real-time reverse transcription polymerase chain reaction [RT-PCR] testing) were included in the overall analysis. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,38,41,42,45,47,[49][50][51][52][53][54][55]58,59,[62][63][64][65][66][67][68][69][70][71]73,76 The pooled prevalence of diarrhea symptoms across these studies was 7.7% (95% CI, 7.2%-8.2%). When analyzing by country (studies from China vs studies from other countries), the pooled prevalence of diarrhea in studies from countries other than China was much higher at 18.3% (95% CI, 16.6%-20.1%).…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
“…In hospitalized patients, across 39 studies including 8,521 patients, the pooled prevalence was slightly higher at 10.4% (95% CI, 9.4%-10.7%) compared with outpatients. [20][21][22][23][25][26][27][28]30,[33][34][35]38,41,42,[44][45][46][49][50][51][52][53][54][55]60,[62][63][64][65][66][67][68][70][71][72][73][74]76 In 3 studies including 1701 outpatients, the pooled prevalence was 4.0% (95% CI, 3.1%-5.1%). 31,59,63 As part of the sensitivity analysis, we identified 35 studies including 9717 patients that described diarrhea, and explicitly reported that it was one of the initial presenting sympto ms. [20][21][22][23][26][...…”
Section: What Are the Gastrointestinal Manifestations Of Covid-19?mentioning
confidence: 99%
“…In addition, two studies consistently demonstrated opposite associations between Type I interferon therapy and clinical outcomes, [30,33] when comparing summary statistics and other included studies. [28,29,31,34,35] Heterogeneity among populations studied may play a role in the disparate individual results, as half of these studies were conducted in China, one was conducted in Iran, five were conducted in Western Europe, and one was conducted in Cuba. Other irreconcilable factors that may have influenced patient outcomes included individual study exclusion criterion, as well as the dosage and delivery method of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of 3 sets of studies with 990, 454, and 1480 patients receiving Type I interferon therapy revealed that there were no significant associations between receiving Type I interferon therapy, compared to standard of care, and ICU admittance, requiring mechanical ventilation, or developing a severe or critical case of COVID-19, respectively (p>0.05; Figure 3B; Figure 3C; Figure 3D). [28][29][30][31][32][33][34][35][36] The analyses included 97, 167, and 537 control patients, respectively. The data exhibited very high heterogeneity in cases of ICU admittance and disease severity (both I 2 >90%), but relatively low in the case of mechanical ventilation (I 2 =12%).…”
Section: Effect Of Interferon Therapy On Clinical Outcomes In Covid-19mentioning
confidence: 99%